2016
DOI: 10.1186/s13321-016-0112-z
|View full text |Cite
|
Sign up to set email alerts
|

vSDC: a method to improve early recognition in virtual screening when limited experimental resources are available

Abstract: BackgroundIn drug design, one may be confronted to the problem of finding hits for targets for which no small inhibiting molecules are known and only low-throughput experiments are available (like ITC or NMR studies), two common difficulties encountered in a typical academic setting. Using a virtual screening strategy like docking can alleviate some of the problems and save a considerable amount of time by selecting only top-ranking molecules, but only if the method is very efficient, i.e. when a good proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 44 publications
2
109
0
Order By: Relevance
“…However, prioritizing according to their ligand efficiencies shows that CTC, CPC and CMC will more efficiently inhibit the activities of the enzyme than ciprofloxacin and chlorobiocin, two approved drug whose mechanism of actions are by the inhibition of DNA gyrase [46]. …”
Section: Resultsmentioning
confidence: 99%
“…However, prioritizing according to their ligand efficiencies shows that CTC, CPC and CMC will more efficiently inhibit the activities of the enzyme than ciprofloxacin and chlorobiocin, two approved drug whose mechanism of actions are by the inhibition of DNA gyrase [46]. …”
Section: Resultsmentioning
confidence: 99%
“…For eliminating the node sets with the weak interaction, we set the threshold variable T to 0.5 based on the previous literature research [45], which means we did not take such links into consideration if the similarity between these nodes was less than 0.5. So that three weighted matrixes can be represented as:…”
Section: Methodsmentioning
confidence: 99%
“…For saving time, we set a parameter L to limit the maximum length of paths. According to previous literature research [45] and comparison experiments, we found that it was suitable to set L = 3 after trying different values from 2 to 4 increasingly, i.e. one path was not allowed to include more than three edges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit, none of these virtual metabolites has a validated MS/MS spectrum, making it difficult to rank the best structure to the experimental MS/MS data. Several research groups have generated tools to predict MS/MS spectra from molecular structures, using chemical bond energies in the improved MetFrag tool [42], known dissociation rules in MS2Analyzer [43], hydrogen bond rearrangements in MS-FINDER [38], fragmentation tree calculations in CSI:FingerID [44] or machine learning strategies in CFM-ID [45 • ]. These tools are tested in regular competitions, the CASMI contests [46].…”
Section: From Elemental Formulas To Correct Epimetabolite Structure Amentioning
confidence: 99%